Combined effect of thermosonication and high hydrostatic pressure on bioactive compounds, microbial load, and enzyme activities of blueberry juice. (March 2022) - Chen, Tianshun; Li, Bin; Shu, Chi; Tian, Jinlong; Zhang, Ye; Gao, Ningxuan; Cheng, Zhen; Xie, Xu; Wang, Jiaxin
The current study is aimed to evaluate the combined effect of thermosonication (TS) and high hydrostatic pressure (HHP) on enzyme activities (polyphenolase and peroxidase), microbial load and phenolic compounds (phenols, flavonoids, and anthocyanins) of blueberry juice. Blueberry juice has been treated with TS (40 kHz and 240 W) at different temperatures (25 °C and 45 °C) for 15 mins with subsequent different HHP (200, 400 and 600 MPa) for 5 mins at room temperature. The results revealed that a combined use of HHP of 400 MPa and 600 MPa with TS at 45 °C not only reduced microorganisms below 1 logCFU/mL, but also significantly inactivated enzymes. The treatments also increased the phenolic compounds, peroxyl radical scavenging capacity (PSC), and DPPH free radical scavenging activity to a higher level without causing any changes in soluble solids and pH. Therefore, the combination of HHP and TS can be used as a novel alternative nonthermal technology to improve the nutritional qualities of blueberry juice, which produces a desirable, healthy juice for consumers.